A novel 3D porous electrode of polyaniline and PEDOT:PSS coated SiNWs for low-cost and high-performance supercapacitors. (5th July 2021) - Shen, Xiaojuan; Zhang, Xuan; Wang, Tongfei; Li, Songjun; Li, Zhaoqiang
Abstract : A novel 3D porous polymer-coated SiNW supercapacitor electrode is developed using a simple and low temperature method. With the optimized charge transfer path, the electrode is first fabricated on a solar-grade Si wafer. Abstract : In this study, a novel 3D porous Si-based supercapacitor electrode was developed using a simple solution method, which involved first the in situ polymerization of polyaniline particles (PANI) on Si nanowire arrays (SiNWs), followed by the further electrodeposition of a polyaniline nanofiber (PANF) film. Highly doped PEDOT:PSS layers were introduced before and after PANF deposition, serving as the built-in 3D current collector of the electrode. To improve the capacity of the electrode, the PANF film was incorporated with graphene and the PEDOT:PSS layer was doped with chloroplatinic acid (H2 PtCl6 ). Due to the smart design, SiNWs only acted as a scaffold, thus the electrodes could be fabricated on any Si-based wafer commonly used in micro-electronic devices regardless of its purity, conductivity and surface passivation. Here, the Si-based supercapacitor electrode was first fabricated on a solar-grade (SG) Si wafer, which exhibited a high areal capacitance of 718.85 mF cm −2 at 1 mA cm −2 . Additionally, an aqueous asymmetric supercapacitor was assembled by using the resultant polymer-coated SiNWs on the SG wafer as the positive electrode, and the activated carbon (AC) as the negative electrode, which exhibited an energy density of 0.194 mW h cm −2 at a power density of 0.85 mW cm −2 . Both of them outperform the reported values of most of the electronic-grade (EG) Si-based electrodes and supercapacitors. This work not only paves a promising way for the design of a 3D electrode, but also opens up a new opportunity to develop low-cost and high-performance Si-based supercapacitors.